The genome sequence of an ichneumonid wasp, Ophion costatus Ratzeburg, 1848 [version 1; peer review: 2 approved] - Gavin R. Broad; Chris Fletcher; Inez Januszczak (Wellcome Open Research)
We present a genome assembly from an individual male Ophion costatus (ichneumonid wasp; Arthropoda; Insecta; Hymenoptera; Ichneumonidae). The genome sequence is 519.4 megabases in span. Most of the assembly is scaffolded into 13 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 25.95 kilobases in length.